Therapeutic SERPINs: Improving on Nature - Maas, Coen; de Maat, Steven (Frontiers in Cardiovascular Medicine, 2021)
Serine proteases drive important physiological processes such as coagulation, fibrinolysis, inflammation and angiogenesis. These proteases are controlled by serine protease inhibitors (SERPINs) that neutralize their activity. Currently, over 1,500 SERPINs are known in nature, but only 37 SERPINs are found in humans. Thirty of these are functional protease inhibitors. The inhibitory potential of SERPINs is in perfect balance with the proteolytic activities of its targets to enable physiological protease activity. Hence, SERPIN deficiency (either qualitative or quantitative) can lead to disease. Several SERPIN resupplementation strategies have been developed to treat SERPIN deficiencies, including concentrates derived from plasma and recombinant SERPINs. SERPINs usually inhibit multiple proteases, but only in their active state. Over the past decades, considerable insights have been acquired in the identification of SERPIN biological functions, their inhibitory mechanisms and specificity determinants. This paves the way for the development of therapeutic SERPINs. Through rational design, the inhibitory properties (selectivity and inhibitory potential) of SERPINs can be reformed and optimized. This review explores the current state of SERPIN engineering with a focus on reactive center loop modifications and backbone stabilization. We will discuss the lessons learned from these recombinant SERPINs and explore novel techniques and strategies that will be essential for the creation and application of the future generation of therapeutic SERPINs.